BORDERS AS BOUNDARIES TO FISCAL POLICY INTERACTIONS? AN EMPIRICAL ANALYSIS OF POLITICIANS' OPINIONS ON RIVALS IN THE COMPETITION FOR FIRMS1. (23rd April 2013) - Geys, Benny; Osterloh, Steffen
ABSTRACT: Studies of spatial policy interdependence in (local) public policies usually concentrate on the relations between jurisdictions within a single analyzed region, and disregard possible extraregional effects. However, the theoretical spatial statistics literature shows that biased estimates might emerge if spatial interactions extend beyond the boundaries of the available data (i.e., the boundary value problem). This paper empirically assesses the practical relevance of this concern by studying German local politicians' assessments of their jurisdictions' main competitors in the struggle to attract firms. We find that location near a border significantly undermines politicians' perception that the fiercest competitive pressure derives from jurisdictions within their own state. This effect sets in about 20 km (10.2 km) from a national (international) border. These results indicate that nearest municipalities perceive each other as competitors regardless of the state or country where they are located, which has important implications for estimating spatial dependence models.